Sistem Pendukung Keputusan untuk Seleksi Penerimaan Dosen menggunakn Metode AHP dan SAW - Lalu Puji Indra Kharisma (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2019)
In fulfilling its vision and mission, STMIK SZ NW Anjani is always striving to improve value and internal quality as a means of strategic intuition to be able to compete with other universities. One of the many ways to improve the overall quality of a university is to improve the recruitment process of lecturers because the quality of the lecturers will determine the overall quality of the university.In order to have a more objective recruitment process of lecturers, the decision support system is being constructed. In this case, the methods that are used to determine an alternative prospective lecturers based on priority are the application ofAnalytical Hierarchy Process (AHP) and Simple Addative Weighting (SAW) methods. AHP is used to determine the weighting criteria, the weighting sub criteria andscoring based on latest education, while SAW is used to find the final result and determining the rank. The final result of using AHP and SAW as a decision support system model is to be able to help the committee leaderin making final decision for the selection.